HUBUNGAN PENGETAHUAN DAN PERSEPSI MASYARAKAT DENGAN UPAYA PENCEGAHAN COVID-19 DI DESA TATELI SATU LINGKUNGAN III KECAMATAN MANDOLANG KABUPATEN MINAHASA - Gumolung, Cintya (Journal Of Community & Emergency, 2024)
COVID-19 is a disease caused by the corona virus which has become a pandemic throughout the world, including Indonesia. Public knowledge and perceptions have a major influence on efforts to prevent this virus outbreak. The purpose of this study was to determine the relationship between knowledge and public perception with efforts to prevent COVID-19 in the Tateli One Village, Environment III, Mandolang District, Minahasa Regency. This type of research uses descriptive analytic research with a "cross sectional" approach. The population in this study is the community in the village of Tateli One Neighborhood III Mandolang District Minahasa Regency totaling 335 people. Sampling the study used a purposive sampling technique with sample calculation using the Slovin formula, obtained as many as 77 people with inclusion criteria, namely people aged 18-60 years and people who were willing to fill out questionnaires, while the exclusion criteria were people who had a history of COVID-19. The data obtained in this study were processed using chy-square with a level of significance (α = 0.05). Based on the results of 77 respondents, the results good category on public knowledge as many as 52 people (67,5%), 25 people (32,5%) have sufficient knowledge, for the good category on public perception as many as 55 people (71,4%), 22 people (28,6%) have a sufficient perception, for the very good category in COVID-19 prevention efforts as many as 45 people (58,4%), 29 people (37,7%) had good prevention efforts and 3 people (3,9%) had sufficient prevention efforts. The conslusion in this study is that the knowledge and perceptions of the community in Tateli One Village, Environment III Mandolang District Minahasa Regency are categorized as good. COVID-19 prevention efforts in Tateli One Village, Environment III Mandolang District Minahasa Regency are categorized as very good. The suggestion for this research is to use it as a source of information and knowledge for the community and it is hoped that the community will establish, improve and have a high awareness of the behavior of COVID-19 prevention efforts.